What can be learned in the snake antivenom field from the developments in human plasma derived products?. (May 2018) - Burnouf, Thierry
Abstract: Human plasma-derived medicinal products and snake antivenom immunoglobulins are unique and complex therapeutic protein products. Human plasma products are obtained by fractionating large pools of plasma collected from blood plasma donors. They comprise a wide range of protein products, including polyvalent and hyperimmune immunoglobulins, coagulation factors, albumin, and various protease inhibitors that are transfused to patients affected by congenital or acquired protein deficiencies, immunological disorders, or metabolic diseases. Snake antivenoms are manufactured from pools of plasma collected from animals, typically horses, which have been immunized against snake venoms. Transfusing antivenoms is the cornerstone therapy to treat patients affected by snakebite envenoming. Over the last thirty years, much technical and regulatory evolution has been implemented to ensure that this class of biologicals meets modern quality requirements. The purpose of this review is to compare the main developments that took place in plasma production, protein fractionation, pathogen safety, quality control, preclinical and clinical studies, and regulations of these products. We also analyze whether both fields have been influencing and cross-fertilizing each other technically and in regulatory aspects to reach modern safety and efficacy standards at global levels, and how experience in the human plasma fractionation industry can further impact the manufacture of snake antivenom and that of other animal-derived antisera. Highlights: Snake antivenoms are the only therapy for rationale and effective treatment of snakebite envenoming. Human plasma fractionation and snake antivenom production share many common features. Technical features/regulations in human plasma fractionation can guide cost-effective GMP-production of safe and clinically-effective animal plasma-derived antivenoms. Human plasma fractionation can serve as bench-mark for quality and virus safety criteria of snake antivenom immunoglobulins.